Frovatriptan 2.5 mg plus dexketoprofen (25 mg or 37.5 mg) in menstrually related migraine. Subanalysis from a double-blind, randomized trial. (January 2015) - Allais, G; Bussone, G; Tullo, V; Cortelli, P; Valguarnera, F; Barbanti, P; Sette, G; D'Onofrio, F; Curone, M; Benedetto, C
Purpose: The purpose of this article is to investigate the efficacy and safety of frovatriptan plus dexketoprofen 25 or 37.5 mg (FroDex25 or FroDex37.5, respectively) compared to that of frovatriptan 2.5 mg (Frova) in menstrually related migraine (MRM). Aim: The aim of this article is to analyze a subgroup of 76 women who treated an MRM attack in this multicenter, randomized, double-blind, parallel-group study. Methods: The primary end-point was the proportion of patients who were pain free (PF) at two hours. Secondary end-points included pain-relief (PR) at two hours and 48 hours sustained pain free (SPF). Results: PF rates at two hours were 29% under Frova, 48% under FroDex25 and 64% under FroDex37.5 ( p < 0.05). PR at two hours was Frova 52%, FroDex25 81% and FroDex37.5 88%, while 48 hours SPF was 18% under Frova, 30% under FroDex25 and 44% under FroDex37.5. Conclusion: Combining frovatriptan+dexketoprofen produced higher PF rates at two hours compared to Frova while maintaining efficacy at 48 hours. Tolerability profiles were comparable.